T Cell Receptor (TCR)-induced Tyrosine Phosphorylation Dynamics Identifies THEMIS as a New TCR Signalosome Component - Brockmeyer, Claudia (American Society for Biochemistry and Molecular Biology, 2011)
Stimulation of the T cell antigen receptor (TCR) induces formation of a phosphorylation-dependent signaling network via multiprotein complexes, whose compositions and dynamics are incompletely understood. Using stable isotope labeling by amino acids in cell culture (SILAC)-based quantitative proteomics, we investigated the kinetics of signal propagation after TCR-induced protein tyrosine phosphorylation. We confidently assigned 77 proteins (of 758 identified) as a direct or indirect consequence of tyrosine phosphorylation that proceeds in successive “signaling waves” revealing the temporal pace at which tyrosine kinases activate cellular functions. The first wave includes thymocyte-expressed molecule involved in selection (THEMIS), a protein recently implicated in thymocyte development but whose signaling role is unclear. We found that tyrosine phosphorylation of THEMIS depends on the presence of the scaffold proteins Linker for activation of T cells (LAT) and SH2 domain-containing lymphocyte protein of 76 kDa (SLP-76). THEMIS associates with LAT, presumably via the adapter growth factor receptor-bound protein 2 (Grb2) and with phospholipase Cγ1 (PLC-γ1). RNAi-mediated THEMIS knock-down inhibited TCR-induced IL-2 gene expression due to reduced ERK and nuclear factor of activated T cells (NFAT)/activator protein 1 (AP-1) signaling, whereas JNK, p38, or nuclear factor κB (NF-κB) activation were unaffected. Our study reveals the dynamics of TCR-dependent signaling networks and suggests a specific role for THEMIS in early TCR signalosome function.